2022
DOI: 10.1177/20499361221080650
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of colistin resistance in carbapenem-resistant Enterobacterales and XDR Klebsiella pneumoniae

Abstract: Introduction: Increasing occurrence of infections caused by multidrug-resistant Gram-negative bacteria resulted in colistin being the last agent for treatment. Apart from plasmid-mediated mcr genes, mutations involving several genes like mgrB, phoP/phoQ, pmrA, pmrB, pmrC, and crrABC genes, are leading causes of colistin resistance. Four colistin susceptibility testing methods were compared against broth microdilution (BMD) and determined the presence of the mcr1-5 gene. Methodology: A total of 100 carbapenem-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
4
10
1
Order By: Relevance
“…This high VME and ME may be due to the use of plastics in this automated system which is shown to absorb the drug to its surface. All the phenotypic methods performed better against E. coli in comparison to K. pneumoniae, as in previous studies [12].…”
Section: Discussionsupporting
confidence: 75%
“…This high VME and ME may be due to the use of plastics in this automated system which is shown to absorb the drug to its surface. All the phenotypic methods performed better against E. coli in comparison to K. pneumoniae, as in previous studies [12].…”
Section: Discussionsupporting
confidence: 75%
“…In this research, antimicrobial susceptibility tests revealed that 28.8% of isolates were resistant to colistin (Table 2) which is lower rather than the result of a study performed by Rad et al (31.7%) in 2020, Iran [18], and is more than the result of a research performed by Bir et al (14.6%) in 2022, India [19], and a study done by Ballen et al (2%) in 2021, Spain [20]. Thus, resistance to colistin has relatively decreased between 2018 and 2022.…”
Section: Discussioncontrasting
confidence: 63%
“…On the contrary, lower rates (18.5% and 23.1%) were reported in other studies 18-19 . K. pneumonia was the most common isolated CRGNB in some studies 20-21 but E.coli was the commonest (56.5% and 50%) in others 17, 22 .…”
Section: Discussionmentioning
confidence: 94%